Integrated omics revealed the altered colonic microenvironment after inhibition of peripheral serotonin synthesis by LP533401 - Yidan Ling; Ziyu Liu; Shuibing Han; Haiqin Wu; Chunlong Mu; Weiyun Zhu (iMetaOmics)
Abstract Gut‐derived 5‐hydroxytryptamine (5‐HT), known as serotonin, plays a crucial role in regulating gastrointestinal functions. However, the impact of disruptions in gut‐derived 5‐HT synthesis on the early gut microbiome and intestinal microenvironment remains unclear. In this study, LP533401, an inhibitor targeting peripheral 5‐HT synthesis, was administered orally to neonatal rats starting at 4 days post‐birth. By day 11, inhibition of gut‐derived 5‐HT resulted in altered colonic morphology, characterized by increased crypt depth and reduced myenteric thickness. To investigate the mechanisms underlying these alterations, we employed a combination of metagenomics, mucosal transcriptome, and untargeted metabolomics on colonic samples. Metagenome profiling revealed an upregulation in the microbial two‐component system (ko02020) and tyrosine metabolism (ko00350), with minimal effects on taxa abundances. Transcriptome profiling analysis indicated the discriminant expression of genes enriched in pathogen infection‐responsive signaling (e.g., Salmonella and Yersinia infection) and the Wnt signaling pathway that affected stem cell proliferation. Consistent with increased crypt depth, marker genes related to cell proliferation were excessively activated. Metabolomics analysis indicated lower ascorbate level and higher succinic acid level, correlating with 5‐HT concentrations and increased crypt depth. Additionally, altered metabolic pathways (e.g., nucleotide metabolism, signal transduction, metabolism of cofactors and vitamins) suggested an impact on the colonic function. In summary, early inhibition of gut‐derived 5‐HT may unfavorably reshape the colonic microenvironment, affecting gut morphology, microbial function, stem cell proliferation, and mucosal metabolism.